The integration of Ethno-RME in MatCityMap application to support students’ learning of system of linear equations: A case of Mangkujo Math Trail - Nurnaningsih, Laila; Prahmana, Rully Charitas Indra; Yunianto, Wahid; Bautista, Guillermo Jr. (Journal of Honai Math, 2024)
In the rapidly advancing digital era, mathematics education must integrate various technological applications to support students' development for the 21st century. However, mere technological integration is insufficient; learning must also involve hands-on activities and real-life experiences to equip students with essential skills. Although many current math lessons incorporate technology, they often overlook students' real-life experiences. Hence, there is a need for mathematics learning approaches that combine technology with student activities and relate them to real-life contexts. Ethno-Realistic Mathematics Education (Ethno-RME) is an innovative approach that uses real contexts as a starting point for learning. This approach can be enhanced by the MathCityMap (MCM) application, making learning more interactive and engaging for students. Therefore, this study explores the potential of MCM by integrating content from the Ethno-RME approach. MCM is an emerging technology that facilitates the exploration of outdoor mathematics, providing students with contextual and real-life problems. The authors developed mathematical tasks based on a café or resort in a district in Central Java. Through Educational Design Research (EDR), mathematical tasks were created using artifacts available in the café and incorporated into the MCM application. Students could access the tasks from their mobile devices and track their locations (math trails). The study focused on the system of linear equations derived from geometrical objects found in the café. The results indicated positive impacts, such as improved students' conceptual understanding and mathematics performance. This study provides evidence of the effectiveness of integrating Ethno-RME with digital technology to support students' learning of mathematics. Further research is needed to explore more ethnomathematics activities integrated into MCM that are suitable for students' backgrounds and locations.